Using a board game “Snake and Lader” to teach speaking descriptive text at the eight grade students of SMPN 2 Wungu - Fathlutfika Trahenar Ratih; Nuri Ati Ningsih (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
This research aims at improving the speaking learning process of the eighth graders of SMP Negeri 2 Wungu through Board Game “Snake and Ladder” in the academic year of 2016/2017 this research used qualitative research because the research wants to describe the implementation of Board Game “Snake and Ladder” in teaching and learning process. This research, the researcher got the data from collecting photos, syllabus, RPP, students’ name and students’ score. They are used to know how to use, what the advantages and what the disadvantages of teaching speaking using  using Board Game “Snake and Ladder” in the eighth graders of junior high school. Then, to collect the data, research need a technique that is called technique of collecting data. There were some instrument used by researcher: observation, interview and documentation. Based on the result of the research, using Board Game “Snake and Ladder” can make students to improve their speaking skill. With this game, the students can make a descriptive text orally. The students also feel confident when they come forwards in front of the class. The students can speak up in front of the class confidently. The students are dared to speak in front of the class because it has been used and the considered classmates as a family. The students are enjoying and having fun. The students are also not bored to be follow the lesson. The students have good respon to the teacher. It makes the students very fun and are not bored  because the game in Board Game “Snake and Ladder” is easy to play. Third, using Board Game “Snake and Ladder” this game was easy to implement in the class. This game makes the lesson understood well by the students. It means that by using Board Game media helps the students to comprehend the material clearly and easily because the media facilitate the students to catch the content of the story. Fourth, using Board Game “Snake and Ladder” is this game make students more active to speak up. It means that by using Board Game “Snake and Ladder” in teaching speaking make the students active follow the teaching and learning process. In this research, the researcher give some suggestion. First, the teacher is sugessted to apply various kinds of teaching techniques in teaching speaking. Second, the institutions are suggested to motivated teacher to apply various kinds of teaching techniques. Third, the students are suggested to be more motivated and serious in learning English. And the last , the other researchers are suggested to make further research especially concerning on teaching speaking through the other game or techniques.